Analysis of Detecting the Authenticity of Money Using the Edge Detection Method - Widianto, Nabella Putri; Indartono, Kuat; Nurhopipah, Ade (PT Mattawang Mediatama Solution, 2024)
One of the factors contributing to the increasing number of banknotes counterfeiting crimes is the technological advancements that have been made in the digital printing industry. Duplications that are very similar and even difficult to distinguish from the original banknote sheet are made easily due to high-quality duplication. Viewing, feeling, and looking carefully at a banknote is the traditional way to check the authenticity of a banknotes. And of course, due to the limitations of human capabilities, such methods are ineffective for many banknotes. Effectively and efficiently, edge detection can be completed by image processing or image processing methods. Using the camera, both real and fake banknotes are transferred. This results in two photos saved as JPG files representing both banknotes. After that, the conversion process to greyscale is carried out, edge observations are made on the image, and then a histogram of both images is created. The results of the histogram were compared and texture was analyzed as judged by the brightness and sharpness of the image. Keywords: Edge Detection, Fake Money, Histogram, Real Money, Texture Analysis.